2023
DOI: 10.1136/jnnp-2022-330707
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Argonaute antibodies as a potential biomarker in NMOSD

Abstract: Background and objectivesNeuromyelitis optica spectrum disorders (NMOSDs) are a group of diseases mainly characterised by recurrent optic neuritis and/or myelitis. Most cases are associated with a pathogenic antibody against aquaporin-4 (AQP4-Ab), while some patients display autoantibodies targeting the myelin oligodendrocyte glycoprotein (myelin oligodendrocyte glycoprotein antibodies (MOG-Abs)). Anti-Argonaute antibodies (Ago-Abs) were first described in patients with rheumatological conditions and were rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…AGO-Abs in patients with NMOSD could aid in the diagnosis, monitoring, and prediction of disease activity (12). A prospective study found that AGO-Abs were detected in 6.7% of patients with NMOSD, concluding that AGO-Abs could serve as a biomarker with high specificity and sensitivity for NMOSD (12). Notably, Moritz et al demonstrated that the ELISA method using an antigenstabilizing protocol is more sensitive compared with CBA, but with the same specificity (25).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…AGO-Abs in patients with NMOSD could aid in the diagnosis, monitoring, and prediction of disease activity (12). A prospective study found that AGO-Abs were detected in 6.7% of patients with NMOSD, concluding that AGO-Abs could serve as a biomarker with high specificity and sensitivity for NMOSD (12). Notably, Moritz et al demonstrated that the ELISA method using an antigenstabilizing protocol is more sensitive compared with CBA, but with the same specificity (25).…”
Section: Discussionmentioning
confidence: 99%
“…This study demonstrated the coalesce of AGO-Abs in NMOSD. AGO-Abs in patients with NMOSD could aid in the diagnosis, monitoring, and prediction of disease activity ( 12 ). A prospective study found that AGO-Abs were detected in 6.7% of patients with NMOSD, concluding that AGO-Abs could serve as a biomarker with high specificity and sensitivity for NMOSD ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After the discovery of anti-AQP4 as a serum marker, NMOSD was separated from MS as an independent disease (6). Since then, the number of publications on NMOSD has increased over the past year, and many articles (37)(38)(39)(40) have been published on its epidemiology, diagnosis, clinical characteristics, treatment regimens, treatment response, and outcomes. "Pathogenesis" was the keyword that burst for the longest time.…”
Section: Discussionmentioning
confidence: 99%